APPLICATION OF THE ABC METHOD TO IMPROVE THE EFFECTIVENESS OF CONTROL OF DRUG INVENTORY FOR BPJS HEALTH PATIENTS - Juli Antasari Br Sinaga; Gayus Simarmata; Adi Suarman Situmorang; Nilam Sari; Angelina Manik (RADJA PUBLIKA, 2022)
This study aims to analyze drug inventory control at Kasih Clinic using the ABC method with the help of POM-QM software for Windows. Based on the Pareto principle, the results of data processing indicate that inventory items can be classified into three main groups based on the contribution of usage value to total inventory costs. Group A consists of five main drug items that contribute the most to inventory value, which is around 87.48%, despite the relatively small number of items. This group requires strict control because it has a significant financial impact. Group B includes two drug items with a cumulative contribution of usage value up to 97.55% and requires periodic monitoring with a medium priority level. Meanwhile, group C consists of most drug items but only contributes around 2.45% of the total usage value, so it can be managed with a simpler control system. Overall, the application of the ABC method has proven effective in identifying drug inventory control priorities objectively and based on economic value, thus supporting more efficient hospital inventory management decisions